Costa Rica and the Escazú Agreement: A History of Persistent Absence - Boeglin, Nicolás (2024)
Costa Rica's failure to ratify the Escazú Agreement, adopted in its own territory in 2018, raises several questions. Aside from the harm caused by this absence to Costa Rica's international image as a country committed to human rights and possessing advanced environmental regulations, there are also a series of purported "arguments" presented by the Costa Rican corporate sector. These arguments are wholly contradicted by the economic reality of the 15 states that have already ratified this regional instrument. Furthermore, the Costa Rican Judiciary has engaged in fanciful interpretations, unnecessarily complicating the approval process of the Escazú Agreement, particularly as expressed by a member of the Constitutional Chamber. Strikingly, her arguments align with those of certain Costa Rican business chambers. In light of this non-ratification, Costa Rica's traditional international leadership in environmental matters is seriously compromised. Meanwhile, following Argentina and Mexico in 2021, Chile in 2022, and Belize and Grenada in 2023, Colombia and Brazil are preparing to ratify the Escazú Agreement in the near future.